The Sensitivity of Joint Inversions of Seismic and Geodynamic Data to Mantle Viscosity. (21st April 2020) - Lu, Chang; Forte, Alessandro M.; Simmons, Nathan A.; Grand, Stephen P.; Kajan, Marie N.; Lai, Hongyu; Garnero, Edward J.
Abstract: Seismic tomography has revealed the existence of large‐scale velocity heterogeneities in the mantle. The interpretation of seismic velocity anomalies in terms of temperature and chemical composition is nonunique. We use geodynamic observations including gravity, plate motions, dynamic topography, and excess ellipticity of the core‐mantle boundary combined with seismic observations to investigate the thermo‐chemical structure of the mantle through joint inversions. An outstanding issue, however, is the physical connection between mantle density anomalies and the surface geodynamic observations, which requires knowledge of the mantle viscosity structure. Here we perform joint inversions assuming different viscosity profiles and examine the dependence of the results on the viscosity. We first assume that mantle heterogeneity is due to thermal variations, which places a constraint on the relation between seismic velocity and density, and we subsequently relax the constraint to allow for potential nonthermal effects. In all of our joint inversions, a nonthermal origin of density anomalies is required to explain the geodynamic data, though the amount varies with the assumed viscosity structure. A common observation is a high‐density chemical signal in the center of the large low‐shear‐velocity provinces at the base of the mantle resulting in a near neutral or slightly dense overall buoyancy there. Using the derived density models and their corresponding viscosity profiles, we also calculate instantaneous mantle flow fields. The predicted flow fields derived from joint inversions are generally similar but are quite different from flow fields using density models derived from a posteriori scaling of pure seismic tomography models. Plain Language Summary: The origin and evolution of Earth's mantle have been long‐standing fundamental questions in geosciences. We use both global seismological and geodynamical (gravity, topography, plate motions, and excess ellipticity of the core‐mantle boundary) data sets to investigate whether lateral changes in mantle structure can be explained solely by temperature variations or whether the mantle must also have significant chemical variations. Our results indicate the presence of chemically distinct mantle anomalies. In particular, we find two large regions at the base of the mantle that appear to be chemically distinct with hot mantle upwellings surrounding them. We also derived several models of 3D density variations in the mantle assuming different viscosity profiles. These models were then used to predict the present‐day mantle convective flow. We show that the mantle viscosity structure does not have a strong influence on the pattern of large‐scale mantle flow. We find, however, that 3D density models derived by simple (1D) a posteriori scaling of tomography models obtained only from seismic data yield predictions of significantly different mantle flow. Key Points: Thermal origin of density anomalies alone cannot explain observed geodynamic data Nonthermal density anomalies are found in the center of the large low‐shear‐velocity provinces Density models derived from joint inversion and from pure seismic inversion lead to different predicted mantle flow fields